Penerapan Relaksasi Nafas Dalam Terhadap Penurunan Nyeri Pada Penderita Gastritis Melalui Aplikasi Teori Florence Nightingale Di Wilayah Kerja Puskesmas Sawah Lebar Kota Bengkulu Tahun 2025 - Holipa, Sinta; Tranando, Hengki (Utami Publisher, 2025)
Gastritis is a condition characterized by acute or chronic inflammation of the gastric mucosa. Gastritis can occur due to excess stomach acid, and stomach pain is caused by mucosal erosion, which can lead to an increase in chemical mediators such as prostaglandins and histamine in the stomach. The incidence of gastritis Indonesia is 40.8%, with a prevalence of 274,396 cases, making it the 10th most common type of gastritis in Indonesia.